Direct Seeding of wheat Using Happy Seeder in Paddy Residue Conditions in Madhya Pradesh, India - , Prashant Shrivastava, Siddarth Nayak, S. R. Sharma, Aashutosh Sharma, Y.R. Khare (Archives of Current Research International, 2024)
Trials were conducted on direct sowing of wheat variety GW-322 through happy seeder in combine harvested rice fields in district Narsinghpur, Madhya Pradesh, during two successive year’s viz. 2015-16 and 2016-17. The control treatment was conventional field preparation after combine harvesting of rice followed by sowing of wheat by seed cum fertilizer drill. District Narsinghpur lies in Central Narmada valley region of India. The average annual rainfall of the district is 1136 mm [1] (Yadav et.al. 2021). Soils of the district come under the vertisol category. Results showed that crop yield and net return under the direct sowing of wheat through happy seeder was higher than that obtained under the conventional method. Direct sowing through happy seeder fetched an average crop yield of 47.45 q/ha whereas under the conventional method it was 43.10 q/ha. The net return under direct sowing through happy seeder was Rs. 59025/- per ha whereas it was only Rs. 48850/- per ha under the conventional method. Happy seeder is an innovative technology and is being widely adopted to reduce stubble problem and conserve soil and environment. The results showed that the direct sowing of wheat through happy seeder performed better than conventional field preparation followed by sowing through conventional seed cum fertilizer drill in combine harvested rice fields.